2021
DOI: 10.1007/s15010-021-01629-2
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: big seroprevalence data from Pakistan—is herd immunity at hand?

Abstract: Purpose Seroprevalence surveys from different countries have reported SARS CoV-2 antibodies below 20% even in the most adversely affected areas and herd immunity cannot be predicted till more than half of the population gets the disease. The purpose of this survey was to estimate the magnitude of community-based spread of the infection, associated immunity, and the future prospects and proximity to a 'herd community'. Methods The study was undertaken as a cluster randomized, cross-sectional countrywide survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…When looking at the proportion of pediatric seroprevalence in a given population, previous studies found conflicting evidence regarding children’s share. Several early works have reported pediatric seroprevalence to be the lowest among age groups [ 40 , 41 , 42 , 43 ]. Likewise, in another Tyrolean hotspot, Ischgl, Knabl et al found a significantly lower seroprevalence in the pediatric population of 27.1% as opposed to 45% in the adult population in April 2020 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…When looking at the proportion of pediatric seroprevalence in a given population, previous studies found conflicting evidence regarding children’s share. Several early works have reported pediatric seroprevalence to be the lowest among age groups [ 40 , 41 , 42 , 43 ]. Likewise, in another Tyrolean hotspot, Ischgl, Knabl et al found a significantly lower seroprevalence in the pediatric population of 27.1% as opposed to 45% in the adult population in April 2020 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after the emergence of SARS‐CoV‐2, a number of large‐scale, population‐based serological studies with random sampling were undertaken to achieve an accurate estimate of seroprevalence. 16 , 17 , 18 , 19 , 20 , 21 , 22 Although studies employing random sampling of households are representative, they are also resource intensive and therefore have often been limited to narrow geographic areas and/or single points in time. CDC pursued a more practical approach based on the use of residual blood specimens from commercial laboratories 23 and blood donors, 3 the latter of which was the design of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The first objective, determining the proportion of the population that has been infected over time, was the most immediate need when the effort began. Shortly after the emergence of SARS‐CoV‐2, a number of large‐scale, population‐based serological studies with random sampling were undertaken to achieve an accurate estimate of seroprevalence 16–22 . Although studies employing random sampling of households are representative, they are also resource intensive and therefore have often been limited to narrow geographic areas and/or single points in time.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Therefore, a seroepidemiological survey is essential to timely estimate COVID-19 virus infection rates, as the good progression of the epidemic in the community will eventually help the policymakers institute effective health measures. 9,10 Given Pakistan's limited testing capability focusing solely on symptom-based PCR tests, seroprevalence studies are required to identify the real scope of the illness and how far we have progressed in attaining herd immunity. Therefore, we undertook this study to estimate the seroprevalence of SARS-CoV2 antibodies in patients and healthy individuals presenting to a tertiary care hospital in Lahore.…”
Section: Introductionmentioning
confidence: 99%